Mechanisms of synergy creation for social-ecological transformation: Leverage point analysis of the emergence of autonomous innovations - Hidetomo Tajima; Tetsu Sato; John Banana Matewere; Dorothea Agnes Rampisela; Motoko Shimagami; Shion Takemura; Mitsutaku Makino (PLoS ONE, 2025)
Transformation of social-ecological systems is required to overcome complex and difficult challenges and move forward toward sustainable futures for humanity and the environment. We have accumulated case examples of autonomous innovations emerging among community members in rural areas of developing countries through transdisciplinary dialogues with innovators. Collective actions among diverse actors in communities are mobilized in these autonomous innovations to promote transformations by creating synergies among resource management practices. Synergy creation has a greater impact on transformations of social-ecological systems because broader people are involved in the network, the range of covered resources and ecosystems is wider, and diverse beneficiaries are involved. We applied a novel approach to visualize leverage points in the emergence processes of synergies in autonomous innovations to understand the pathways and mechanisms of social-ecological transformation driven by these innovations. We made comparisons of 17 cases of autonomous innovations with and without synergies to clarify the mechanisms of social-ecological transformations through synergies. The process of synergy creation was complicated and several factors in the initial phases of autonomous innovations interact with each other to generate synergies. These factors included perception changes of people and innovators and visualization of new challenges. We also found that diverse functions of leverage points appearing at the initial phases played critical roles in synergy creation. Functions related to synergy creation such as the visualization of challenges, creation of values, and promoting changes of perceptions were important. Based on these analyses, we propose six guiding principles for local practitioners, community-based innovators, and transdisciplinary scientists collaborating with these actors to promote the transformation of social-ecological systems through the creation of synergies in autonomous innovations.